Solidariedade e interesses na gestão de recursos hídricos - Matilde de Souza (2004)
This work considers as study object the water resources politics of Minas Gerais State in order to discuss its main organ, Comitê de Bacia Hidrográfica, as an adequate institution to the production of public goods in this field. The work analyses comparatively three committees which have different paths, however similar problems in their action areas. From the presumption that environmental politics are related to the production of public goods, this research is developed from pertinent theoritical and from the exposition of national and state water politics through the study of three committees already mentioned, using among others, information collected from their members. This study brings an approach about Water Resources Brazilian Politics, Minas Gerais State water resources politics and discusses the foundation process of committees, the interaction rules of their members and strategies adopted by their actors who belong to them and face the necessity to promote the interests of the sector they represents as well as the interests of the collective. Thus, it is the aim herein to discuss if the Comitê de Bacia Hidrográfica is an institution able to make co-operation a racional strategy of actors with different and controversial